Developing a murine model for Q fever - Benson, Jeret, author; Bowen, Richard, advisor; Duncan, Colleen, committee member; Jones, Robert, committee member; Van Metre, David, committee member (Colorado State University. Libraries, 2011)
Coxiella burnetii is a gram-negative, intracellular bacterium that causes disease in humans and animals. The bacterium is commonly found in nature and humans and animals develop infections by inhaling infectious aerosols. Animal infections are generally asymptomatic, but the organism can induce abortion in pregnant sheep, goats, and cattle. Human infections, called Q fever, can induce mild to moderate disease, and lifelong infections may develop. Research to characterize this bacterium has been difficult due to its intracellular nature, and studying experimental infections in animal models has provided important information about the bacterial lifecycle and pathogenesis of the disease. The studies described here focused on evaluating a number of facets of C. burnetii infection in C57BL/6 inbred mice. Infections were determined through immunofluorescence detection, quantitative PCR assays, and histopathologic analysis. Mice developed similar histopathologic lesions as humans, specifically hepatitis, interstitial pneumonia, and myocarditis when infected by intranasal inoculation with the Nine Mile phase I strain of the bacterium. Detection of bacterial DNA in tissues and frequency of histopathologic lesions were highest two weeks after infection, with a significant decrease observed 42 and 59 days after infection. Mouse age and chemically induced immunosuppression with dexamethasone or cyclophosphamide were evaluated in C. burnetii infected mice to determine if these factors exacerbated disease. These studies revealed that neither age, (nine-weeks versus nine-months), or chemically induced immunosuppression (dexamethasone versus cyclophosphamide) significantly enhanced disease manifestations in infected mice. Additionally, antimicrobial treatment with doxycycline was evaluated in treating C. burnetii infections in mice. Such treatment reduced splenic pathology but did not significantly reduce the frequency of other histopathologic lesions or the amount of bacterial DNA detected in tissues. Overall, C57BL/6 mice infected by intranasal inoculation develop histopathologic lesions similar in many respects to what is observed in infected humans. However, disease manifestations were not exacerbated by host age or the immunosuppressive treatments investigated. Additionally, the dose of doxycycline received by mice was only marginally effective in treating bacterial infection in mice.
Keywords: coxiellosis; Coxiella burnetii; Q fever